2010
DOI: 10.1007/s00586-010-1383-0
|View full text |Cite
|
Sign up to set email alerts
|

The influence of torsion on disc herniation when combined with flexion

Abstract: The role of torsion in the mechanical derangement of intervertebral discs remains largely undefined. The current study sought to investigate if torsion, when applied in combination with flexion, affects the internal failure mechanics of the disc wall when exposed to high nuclear pressure. Thirty ovine lumbar motion segments were each positioned in 2°axial rotation plus 7°fl exion. Whilst maintained in this posture, the nucleus of each segment was gradually injected with a viscous radioopaque gel, via an inject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
44
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(48 citation statements)
references
References 49 publications
3
44
0
1
Order By: Relevance
“…The comparison between these results with the failure pressure of the annular fibers reported in previous studies for several MS models (Table 2) reveals that the values documented on this report are appreciably lower than the more recent studies, performed by Schechtman et al (2006) and Veres et al (2010). In fact, several studies reported the magnitude of the rupture values obtained in this study as within the normal range of physiological IDP for human samples (Claus et al, 2008;Dennison et al, 2008;Sato et al, 1999;Wilke et al, 1999).…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…The comparison between these results with the failure pressure of the annular fibers reported in previous studies for several MS models (Table 2) reveals that the values documented on this report are appreciably lower than the more recent studies, performed by Schechtman et al (2006) and Veres et al (2010). In fact, several studies reported the magnitude of the rupture values obtained in this study as within the normal range of physiological IDP for human samples (Claus et al, 2008;Dennison et al, 2008;Sato et al, 1999;Wilke et al, 1999).…”
Section: Discussionsupporting
confidence: 63%
“…Few studies include the determination of the failure pressure of the IVDs (Iencean, 2000;Menkowitz et al, 2005;Schechtman et al, 2006;Veres et al, 2010). Schechtman et al (2006) investigated the intrinsic failure strength of the intact bovine caudal disc using an hydraulic inflation actuator.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Whilst torsion alone may not pose a threat to the structural integrity of lumbar intervertebral discs, it appears to have a marked effect when applied in conjunction with flexion [31].…”
Section: Discussionmentioning
confidence: 97%
“…Using finite element analysis, Schmidt et al [33] found that under this same loading combination, flexion plus left axial rotation, the fibres of the inner right posterolateral annulus experience the largest shear strain. Various biomechanical studies have demonstrated that the combination of flexion and torsion is capable of producing injury to the posteriolateral annulus [31,34].…”
Section: Discussionmentioning
confidence: 99%